The Medicolegal Evaluation of Splenic Lesions and Diagnostic Criteria of Blunt Abdominal Trauma in Children Treated Conservatively - Durak, Dilek; Çoltu, Atınç; Fedakar, Recep (The Bulletin of Legal Medicine, 1996)
In this study; we aimed to determine whether the diagnosis and treatment protocols related to blunt abdominal trauma and splenic injury cause any changes in the view of Forensic Medicine. We evaluated the files of 58 blunt abdominal trauma cases that are followed up by the Department of Pediatric Surgery of Medical Faculty of Uludağ University among 1988-1993. Out of 33 cases (%57) who had intraabdominal hemorrhage by the virtue of blunt abdominal trauma, splenic injury is identificated in 16 cases (%48). 12 cases (%75) with splenic injury were treated conservatively, whereas 4 (%25) had an operation. In the treatment protocol, CT, US, peritoneal lavage, hemoglobin, hematocrite values are evaluated. The literature data concerning the blunt abdominal trauma is reviewed, the diagnosis and treatment methods are determinated and evaluated in the view of Forensic Medicine. Keywords: Intraabdominal Hemorrhage, Conservative Treatment, Blunt Abdominal Trauma, Splenic Trauma, Children.